The mystery of the writing process: a comparison of mechanistic and developmental organic writing - Yaacob, Solehah@Nik Najah Fadilah; Haron, Ismail; Yaacob, Adli; Hussain Awdah AlQahtani, Zainah (Primrose Hall Publishing Group, 2022)
Every writer knows putting words on paper is a difficult task. Sometimes the difficulties become insurmountable. He got himself into a state of frustration in writing when the flow of ideas stopped. A writer got stuck and banged his head against the wall for long hours instead of writing. His struggle becomes futile without getting the desired result. Despite being armed with knowledge and language ability, he cannot execute his task. The objective is primarily to understand the cognitive processes in writing employing different approaches: mechanistic writing and developmental organic writing models. This understanding is derived and inferred from some learning theories such as the behaviourist and mechanical models coupled with issues related to the functions of brains and ‘mind’ in writing as expounded by some known linguists and writers. It is hoped that by understanding the cognitive processes at work in writing, anyone who intends to write can benefit in terms of enhancing his writing skill and making writing a challenging and enjoyable task. The study is on a qualitative analysis of abook written by Peter Elbow on `Writing Without Teachers` and `Writing with Power`. Compared to the researchers, the data collected from his experiences will embark on the meaning of `organic writing`.